THE USE OF NANO-COATING IN THE MODIFICATION OF STEELS - V. N. Kovalevsky; A. E. Zhuk; A. V. Kovalevskaya; S. V. Grigoriev; A. I. Ilukevich (Литьë и металлургия)
The problems of applying nanolayers of tungsten, molybdenum, cobalt, silicon carbide, carbon, applied by magnetron distribution system on the powders of iron groups, followed by their introduction to the steel melt. The structure and properties of a coating modifier and its impact on the structure and properties of the steel are studied